Analisis Kualitas Situs Web Dinas Komunikasi dan Informatika Kabupaten Nabire dalam Penyediaan Informasi Publik - Agung Nurrahman; Febrie Nabiani Bagau (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2023)
The Website is provided as one of the means of providing public information provided by local governments in providing information about government activities and information about other local governments. The Nabire Regency Office of communication and Information Technology uses the website as a media for public services and needs to measure its quality. The purpose of this study was to develop and apply an overview of the quality of the website in the provision of information on the Department of communication and information Nabire Regency. This research method uses quantitative research methods with descriptive research type. Data collection techniques using observation, interviews and documentation. The process of data analysis includes data preparation, data preparation and conclusion preparation. The findings of the study show that the Nabire Regency information and Communication Office website has provided various information, especially information about events that occurred in Nabire Regency. However, there are still some changes made to the regulation of the amount of human resources that can operate the website, lack of socialization done for the community, especially related to the use of the website. But on the other hand, there is support from each department/regional agency, especially in terms of providing data and information to be used on the website of the Nabire Regency Communications and Information Office. The conclusion of the study shows that the quality of the website of the Office of communication and information Nabire Regency of central Papua province is included in the sufficient category.